Factores que influyen en la transformación digital en las instituciones de educación superior. Universidad Nacional de Colombia sede Bogotá (2021)
Digital transformation enables organizations to stay and compete in the marketplace through organizational change. In the case of Higher Education Institutions, especially the factors that may influence a digital transformation process in these institutions have not been identified. The present research aims to identify these factors, under the Mingers multimethodology, the Yin case study and the Delphi method. The Research was developed in 3 stages, namely: the first stage corresponded to the systematic review of the literature on the digital transformation process focused on the factors that influence this process and its characterization. In the second stage, the evaluation of the factors identified in the literature review by experts was carried out under the Delphi method, applied to a Higher Education Institution, taking the National University of Colombia Headquarters Bogotá as a case study. In the third stage, the factors agreed upon by the participating experts were consolidated. The identification of these factors will serve as input to initiate a process of digital transformation in Institutions of Higher Education.